Comparative effectiveness of open versus laparoscopic resection in patients with locally advanced colon cancer: Inverse probability of treatment weighting approach - Mesnad S. Alyabsi; Anwar H. Alqarni; Adel F. Almutairi; Mohammed S. Alhalafi; Mohammed A. Algarni; Kanan M. Alshammari; Nahar A. Alselaim (PLoS ONE, 2025)
Background In Saudi Arabia, colorectal cancer is one of the most common cancers. Most of colorectal cancer cases were diagnosed at an advanced stage, making the treatment process more challenging. In this paper, we aim to investigate the differences between open and laparoscopic colectomies and factors influencing the use of these approaches in locally advanced colon cancer patients. Methods The study population included patients with locally advanced colon cancer at the National Guard-Health Affairs, Saudi Arabia. Descriptive and clinical data were collected for the patients diagnosed with locally advanced colon cancer from 2016 to 2021. The variables related to the locally advanced colon cancer patients’ characteristics were compared with a chi-square test, Fisher’s exact tests, student’s t-tests, or Wilcoxon tests when appropriate. The overall survival and recurrence-free survival were computed using the Cox regression model. Results Of the 222 patients who underwent tumor resection, 75 (33.8%) underwent a laparoscopic colectomy. Unlike open colectomy patients, the group with laparoscopic colectomy were younger, had a higher body mass index, and had tumors in the left colon, with ≥12 harvested lymph nodes. The weighted data indicated no difference in the 5-year overall-survival, and the recurrence-free survival between the approaches [5-year overall survival, hazard ratio: 0.42, 95%CI (0.16, 1.12); recurrence-free survival, hazard ratio: 0.74, 95%CI (0.31, 1.78)]. Conclusions No significant differences were observed between laparoscopic and open surgical approach for patients with locally advanced colon cancer.